CONNECTING THE DOTS: CSR, JOB SATISFACTION, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rumapea, Valentine; Yanuar, Yanuar (Graduate Program of Universitas Tarumanagara, 2024)
Corporate Social Responsibility (CSR) is garnering increasing attention within the realm of business and organizations, owing to its substantial impact across various dimensions, including Organizational Citizenship Behavior (OCB) and Job Satisfaction (JS). This quantitative study was designed to investigate the direct relationship between perceptions of CSR and OCB, as well as the mediating role of JS. The research encompassed 192 respondents hailing from Bank Mandiri, BNI, and BRI, employing a non-probability sampling method. Data collection was facilitated through the distribution of questionnaires via Google Forms, while data analysis was executed using the SmartPLS3. The study's outcomes indicate that employees' perceptions of CSR in these corporations, exert a positive influence on JS and stimulate voluntary OCB. Effective CSR practices are shown to elevate JS, subsequently resulting in heightened OCB, thereby bestowing favorable impacts upon these organizations.